Howard Watkins' Retirement from Fresno-Merced Counties Legal Services Dinner at Yen Ching Restaurant - Watkins, Howard::::::::: (1985)
On left: Sharon Blumberg, Stephen Blumberg, ?; on right: Mary Ludy, Ray Starks, David Cisneros, Nancy Currier